Components of Translation Competence: A Job Task Analysis - Farahzad , Farzaneh; Jazeb, Mohsen (Iranian Journal of Translation Studies, 2021)
Translator training programs—whether at universities or higher education institutes—have been mushrooming in Iran. The avowed objective of these programs is to prepare trainee translators for the competitive market. This article attempts to identify sub-competences of Translation Competence. To this aim, a job task analysis is conducted. First, a 12-member focus group are asked to set forth all a translator need to function competently—this involves filling out a 3-question survey followed by online interviews which have been recorded. Then, based on the data from the survey, a 50-item questionnaire is developed and distributed among professional translators to rate the items in terms of their importance. Finally, the results are discussed and compared with the PACTE’s Translation Competence model. The results of the study show four categories of Knowledge, Skills, Abilities and Attributes, the majority of which are considered necessary for the success of a translator. Also, there is a significant correlation between the results of the present study and PACTE’s Translation Competence model.